The Rejection of Sterility. A Contribution to the Identification of Hedonic and Vital Values in the Gender Dispute - Rozwadowski, Łukasz (Hybris, 2025)
The article adopts a perspective in which relations between values are examined on a basis of cultural products and practices. The object of analysis is the gender dispute, which is treated as an axiotic space, which is a place of differing realizations of the same response to a value, or of divergent stances regarding the same tension between values. The tension central to the text is that between hedonic and vital values – a distinction drawn from Max Scheler’s axiology. This distinction reveals that while the prioritization of hedonic values clearly differentiates the opposing sides of the debate, both anti-gender rhetoric and feminist-queer thought (considered as a whole) perceive “disembodied” ideas of the subject as a threat to the vitality of individuals and societies. This differentiation also proves useful in framing the question of how images of vaginas and, more broadly, women’s bodies—used in confrontation with patriarchy – relate to the sphere of pleasure.